Oral Habits That Cause Malocclusion Problems - Joelijanto, Rudy (Insisiva Dental Journal, 2012)
Oral habits that place pressure on the teeth may slowly move the teeth out of place. The aim of this study was to review the literature for articles referring the most common oral habits that cause malocclusion. The oral bad habits that cause malocclussion problems include: Thumb sucking, It is a normal habit for babies, but causes serious orthodontic problems if it continues long after the eruption of permanent teeth. Prolonged thumb sucking can create crowded, crooked teeth, or bite problems and speech problems. Protrusion and displacement of front teeth are usual results of thumb sucking. Lip-biting or fingernail biting, both habits can shift the teeth out of alignment. Tongue thrusting, some children thrust their tongue forward, pressing it against the lips with a force that can result in teeth malocclusions such as âopen biteâ or teeth protrusion (overjet). While parents can not do much to prevent an orthodontic problem caused by hereditary factors, they can help their kids to avoid the need for braces, by maintaining good oral hygiene and avoiding bad oral habits that could cause teeth malocclusion problems. Modern orthodontics are usually able to treat most teeth malocclusions successfully, but prevention can help the family to avoid the large cost of orthodontic treatment and the child will not have to wear dental braces and feel uncomfortable.